1996
DOI: 10.1017/s0033291700037697
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive dysfunction in chronic schizophrenia followed prospectively over 10 years and its longitudinal relationship to the emergence of tardive dyskinesia

Abstract: SynopsisBasic cognitive function was assessed at initial and at 5- and 10-year follow-up assessments among 41 primarily middle-aged in-patients manifesting the severest form of schizophrenia; additionally, the presence and severity of tardive dyskinesia was evaluated on each occasion. Overall, there was a modest but significant deterioration in cognitive function over the decade, particularly among older men. Longitudinally, patients with persistent tardive (orofacial) dyskinesia continued to show poorer cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 32 publications
4
38
1
Order By: Relevance
“…The fact that 40% of the present sample did not manifest TD despite a duration of neuroleptic exposure and an average duration of mental illness exceeding 40 years clearly suggests that individuals dier in their susceptibility to the disorder. Consistent with previous reports (Hayashi et al, 1996;Smith and Baldasserini, 1980;Waddington and Youssef, 1996), patients with TD were on average older than those without. Mean MMSE scores did not dier between groups of patients with and without TD as de®ned by the criteria of Schooler and Kane; however, MMSE scores were signi®cantly lower in subjects who met the criteria of Waddington and Youssef (1996) for orofacial TD.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The fact that 40% of the present sample did not manifest TD despite a duration of neuroleptic exposure and an average duration of mental illness exceeding 40 years clearly suggests that individuals dier in their susceptibility to the disorder. Consistent with previous reports (Hayashi et al, 1996;Smith and Baldasserini, 1980;Waddington and Youssef, 1996), patients with TD were on average older than those without. Mean MMSE scores did not dier between groups of patients with and without TD as de®ned by the criteria of Schooler and Kane; however, MMSE scores were signi®cantly lower in subjects who met the criteria of Waddington and Youssef (1996) for orofacial TD.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous reports (Hayashi et al, 1996;Smith and Baldasserini, 1980;Waddington and Youssef, 1996), patients with TD were on average older than those without. Mean MMSE scores did not dier between groups of patients with and without TD as de®ned by the criteria of Schooler and Kane; however, MMSE scores were signi®cantly lower in subjects who met the criteria of Waddington and Youssef (1996) for orofacial TD. When the individual orofacial regions (ie face, lips, tongue, jaw) were examined separately, MMSE scores were found to be signi®cantly lower in subjects with abnormal movements of the lips, and a trend in the same direction was seen for subjects with lingual involvement.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Early descriptions of schizophrenia by Emil Kraepelin as ''dementia praecox'' led to the contention that cognitive deterioration occurs beyond that found in the initial stages of the illness. Some early studies indicated progressive decline in neurocognitive function with age 9,10 but this has been disputed with indications that deficits later in life are typical of normal aging. [11][12][13] (Irani, et al, unpublished data) Furthermore, postmortem data from elderly patients with schizophrenia has not shown excess of those neuropathological abnormalities found in typical neurodegenerative disorders such as Alzheimer's disease, 14 yet chemical markers such as cortical amines and neuropeptides deficits have been associated with more severe cognitive dysfunction in some patients.…”
Section: Introductionmentioning
confidence: 99%